GERMAN â€œTREUHANDâ€ VIS-Ã-VIS AUSTRIAN â€œTREUHANDâ€ (TERMINOLOGICAL STUDY) - Gvelesiani, Irina (European Scientific Journal, ESJ, 2015)
The trust is an â€œequitableâ€ concept, which was initially administered by the Court of Chancery. It historically developed in the English common law and gradually crept into some systems of civil law jurisdiction. However, the civil legislations have not fully acknowledged the common law mechanism and created approximate â€œcounterpartsâ€ â€“ the so-called trust-like mechanisms. The given paper makes an attempt to study innovative processes of the European legal system. It highlights the peculiarities of the â€œtrust-likeâ€ mechanisms of the German and Austrian laws. The major emphasis is put on the terminological elements denoting different components of entrusting relationships. The investigation shows, that on the one hand, some Austrian terms (Treuhand, Stiftung, ErmÃ¤chtigungstreuhand, etc.) coincide with the German lexical system and on the other hand, they are similar to the terms of the Roman law.